Take lots to live or to sell? Land trafficking and clientelistic practice in the urban periphery - Pimentel Sánchez, Nekson (2020)
This article deals with patronage-based relations and their correlation with land trafficking in the outskirts of the city of Lima. What are the characteristics and structure of clientelism? What are the forms, agents and mechanisms of land trafficking? These questions will provide an account of the production of the city caught up in a series of transactions that may involve various agents and levels of specialization in the of land seizing and the construction of urban settlements on the outskirts of Metropolitan Lima.